Correction to: Short-term outcome associated with disease severity and electrolyte abnormalities among critically ill children with acute kidney injury - Osama Y. Safdar; Khalid A. Alhasan; Mohamed A. Shalaby; Norah Khathlan; Suleman A. Al Rezgan; Amr S. Albanna; Jameela A. Kari (BMC Nephrology, 2020)
Following publication of the original article [1]